Imla dan Komputer Arab Sebagai Transformasi Mata Kuliah Kitabah Mubtadi di UIN Raden Fatah Palembang - Qoim Nurani; Muhammad Alfath Qaaf; Ahmad Saiful Aripin (Khazanah Multidisiplin, 2023)
The Kitabah lil mubtadi course is a special course in the Arabic language education study program. In the 2022 academic year, this odd semester course will undergo a transformation into Arabic Imla and Computer courses. This is the background of this research so that it needs to be studied in depth to describe the transformation or changes in this course. This research is a library research that uses inductive-deductive analysis techniques. This study aims to reveal Arabic Imla and Computer courses as a transformation of special Arabic science courses. The results of this study indicate that the change in this course is a form of responding to the demands of national qualifications at the undergraduate level. This course focuses on digitizing the ability to write Arabic in a sentence and paragraph that is contained in the software offline and online. Imla and Arabic Computers are also a manifestation of the integration of science, religion, technology.